An empirical analysis of conservation practices, management and sustainability in the Sundarbans Mangrove Forest, Bangladesh. (2015) - Roy, Anjan Kumer Dev; Alam, Khorshed; Gow, Jeff
This article examines the factors that influence conservation practices in the world's largest mangrove forest, the Sundarbans in Bangladesh. It explores the relationship between tree density reductions and management practices. 412 households in forest-dependent communities (FDCs) were interviewed. Their overwhelming view is that the Sundarbans is being over exploited through overharvesting. Results show that FDCs who engage in resource harvesting under the current property rights regime have less participation in and lower motivation for the conservation of forest resources. Current management by the forest department results in lower commitment by the community to conservation. Conservation of resources could be achieved by the allocation of expanded property rights to give management roles to communities. With the granting of these rights they would engage in conservation practices. The results suggest that constructing effective strategies to promote mangrove conservation require these two factors to be addressed to achieve sustainable forest management.